Electrochemical Oxidation/Disinfection of Urine Wastewaters with Different Anode Materials - Sondos Dbira (16488920) (2019)
In the present work, electrochemical technology was used simultaneously for the deactivation of microorganisms and the destruction of micro-pollutants contained in synthetic urine wastewaters. Microorganisms (E. coli) were added to synthetic urine wastewaters to mimic secondary treated sewage wastewaters. Different anode materials were employed including boron-doped diamond (BDD), dimensionally stable anode (DSA: IrO2 and RuO2) and platinum (Pt). The results showed that for the different anode materials, a complete deactivation of E. coli microorganisms at low applied electric charge (1.34 Ah dm−3) was obtained. The complete deactivation of microorganisms in wastewater seems to be directly related to active chlorine and oxygen species electrochemically produced at the surface of the anode material. Complete depletion of COD and TOC can be attained during electrolyses with BDD anode after the consumption of specific electric charges of 4.0 and 8.0 Ah dm−3, respectively. Higher specific electric charges (>25 Ah dm−3) were consumed to removal completely COD and about 75% of TOC during electrolyses with DSA anodes (IrO2 and RuO2). However, the electrolysis using Pt anode can partially remove and even after the consumption of high specific electric charges (>40 Ah dm−3) COD and TOC did not exceed 50 and 25%, respectively. Active chlorine species including hypochlorite ions and chloramines formed during electrolysis contribute not only to deactivate microorganisms but also to degrade organics compounds. High conversion yields of organic nitrogen into nitrates and ammonium were achieved during electrolysis BDD and DSA anodes. The results have confirmed that BDD anode is more efficient than with IrO2, RuO2 and Pt electrodes in terms of COD and TOC removals. However, higher amounts of perchlorates were measured at the end of the electrolysis using BDD anode. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma12081254